Circulating serum chemerin levels are elevated in lipodystrophy. (15th December 2015) - Miehle, Konstanze; Ebert, Thomas; Kralisch, Susan; Hoffmann, Annett; Kratzsch, Jürgen; Schlögl, Haiko; Stumvoll, Michael; Fasshauer, Mathias
Summary: Objective: Lipodystrophy (LD) is characterized by loss of adipose tissue, dysregulation of adipokines and severe metabolic complications. Regulation of the insulin resistance‐inducing and proinflammatory adipokine chemerin has not been assessed in LD. Therefore, we determined chemerin serum levels in LD, chemerin mRNA expression in insulin‐sensitive tissues of LD mice, as well as the impact of metreleptin treatment on circulating chemerin in LD patients. Research Design and Methods: Serum chemerin, as well as clinical and biochemical parameters of glucose metabolism, lipid metabolism, and inflammation, was measured in 37 LD patients and 37 age‐, gender‐ and body mass index‐matched controls. Furthermore, chemerin mRNA expression was determined in LD mice and controls. Moreover, circulating chemerin was assessed at five different time points in 10 LD patients treated with metreleptin over 1 year. Results: Median serum chemerin levels were significantly higher in 37 subjects with LD (234·3 μg/l) as compared to controls (204·0 μg/l) ( P  = 0·002). Multiple linear regression analysis showed that circulating chemerin was independently and positively associated with glycosylated haemoglobin A1c (HbA1c) and C‐reactive protein (CRP). Chemerin mRNA expression was significantly increased 2·5‐fold in visceral adipose tissue (VAT) and 5·3‐fold in brown adipose tissue (BAT) of LD mice as compared to controls ( P  < 0·01). Circulating chemerin was not significantly altered by metreleptin treatment. Conclusions: Circulating levels of the adipokine chemerin are elevated in LD, as well as independently and positively associated with HbA1c and CRP. Increased chemerin might originate from VAT and BAT.